Versatile retraction mechanics: Implant assisted en-masse retraction with a boot loop - Pramod Philip; Nidhin Philip Jose (Wolters Kluwer Medknow Publications, 2015)
The purpose of this paper is to explain the versatility offered by the use of arch wires with boot loops in retraction mechanics while taking direct anchorage from mini-screws. Materials and Methods: The materials include the mini screws placed at the appropriate location and retraction arches made of 0.019 X 0.025 SS with boot loops placed distal to the lateral incisors. Mini screw provides a stable anchorage for enmasse retraction of the anterior teeth with the help of a boot loop using sliding and/or loop mechanics. Results: The arch wires with boot loops have a definite advantage over the soldered/ crimpable hooks because of the versatility it offers during the process of retraction. Conclusion: An innovative approach combining the advantages of absolute anchorage using mini implants and a retraction arch with boot loop is presented here.